PROMOTING OF COST-EFFECTIVE DEVELOPMENT OF INDUSTRIAL ENTERPRISES BY MEANS OF TAX REGULATION - Tsurkan, I. M. (Science and Transport Progress, 2006)
The article has analyzed the Ukrainian taxation system in terms of creating favorable tax conditions for industrial development. On the basis of Ukrainian tax system analysis and generalization of foreign experience in the field of stimulating industrial enterprises, the ways of increasing tax-driven incentives for industrial development have been determined.